Do I really need this transthoracic ECHO? An over-utilized test in trauma and surgical intensive care units. Issue 5 (May 2022) - Gallaher, Jared; Stone, Lucas; Marquart, Grant; Freeman, Christopher; Zonies, David
Highlights: Diagnostic transthoracic echocardiogram is a commonly used exam in a surgery-trauma intensive care unit. A majority of these exams are normal and do not lead to a change in clinical management. Certain patient factors, such as troponin level, may be help differentiate which patients would benefit from this diagnostic tool. Abstract: Introduction: Clinical use of transthoracic echocardiogram (TTE) in intensive care units (ICU) has dramatically increased without clear guidance on validated assessment indications, appropriateness, and patient value. Methods: A retrospective analysis of consecutive TTEs performed among patients admitted to a tertiary trauma/surgical ICU over 2.5 years was performed. A bivariate analysis and Poisson regression was used to compare patients who received a TTE. Sensitivity analysis was performed to assess patient factors that predict change in management based on TTE. An abnormal exam was defined as having at least one of the following: ejection fraction < 55%, wall motion, pericardial effusion, pericardial effusion, or other significant abnormality including filling defect. The effect on management was derived from clinical course. We hypothesize that these studies are usually normal and rarely lead to changes in clinical management. Results: 912 TTEs were performed in 806 patients. The median age was 68 years (IQR 57, 77) and 63.5% were male. Syncope (21.7%) or hypotension/hypovolemia (20.5%) were the most common indications for a TTE. In total, 39.4% TTEs were abnormal and only 7.6% resulted in a change in management. Predictive factors associated with an abnormal exam included: age >50, serum troponin ≥0.1 ng/ml, abnormal ECG, and clinical suspicion of heart failure or acute myocardial infarction. A troponin cutoff level <0.25 ng/mL was the most reliable factor to predict no change in management after TTE with a negative predictive value of 94.3% (95% CI 93.1, 95.3). Conclusion: TTE is commonly used for patient assessment in critically ill surgical patients but the majority of exams are normal without change in clinical management. Certain patient factors, such as troponin level, may help distinguish which patients would benefit from this diagnostic test. Given the considerable cost associated with TTE and the minimal effect on management, guidelines on appropriate use would provide improved patient value.